Digital Diplomacy as a Tool for Empowering Governments: Formulating a Strategy for the Islamic Republic of Iran - Fatemeh Taghavi Ramezani; Mohammad Soltani Far; Hassan Darzban Rostami; Hamid reza Hossini dana (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2023)
Introduction                                   The information revolution has significantly altered the nature of power by enhancing the capacity of soft power and reshaping the very foundations of power structures. In the past, leaders and politicians were the primary figures to determine national interests in each nation, but in the digital age, the Internet and social networks have functioned to eliminate the mediatorship, leading to the highlighted role of the individual, the emergence of public opinions, and distribution of power from the government to people and other key actors. Today, power derived from public opinions is considered by political actors as a potent instrument for accomplishing political objectives.Iran’s Twenty-Year Vision Document, looking ahead to 2025, outlines a comprehensive objective of the Islamic Republic of Iran as to attain a preeminent economic and technological position in the region while preserving its Islamic and revolutionary identity, being a source of inspiration in the Islamic world, and engaging in a constructive interaction in international relations. To secure the top economic position in the region and an influential position in the international arena, it is imperative to leverage the capabilities of the country’s diplomatic apparatus. Diplomacy serves as the executive arm of foreign policy within the framework of a country’s foreign policy doctrine. To thrive in the evolving global landscape requires possessing modern tools since the shifting global landscape demands novel tools and approaches. In today’s world, powerful governments employ soft power instruments to influence and sway societies.Diplomacy stands as one of the most critical tools for advancing a country’s national power and achieving its objectives. Leading governments have embraced digital diplomacy as a means to bolster their national brand and effectively manage their public image, thus reaching vast audiences. In the contemporary age of communication, a formidable presence on the global stage necessitates the strategic implementation of digital diplomacy, positioning it at the forefront ofa country’s public diplomacy initiatives. In this respect, the present research aimed to recognize the role of digital diplomacy as a pivotalpower-building instrument, and to incorporate it into Iran’s strategic planning.This research intended to offer a full-brown description of digital diplomacy by delving into the power-building factors of modern media. The objective was to formulate effective strategies that enhance the digital diplomacy initiatives of the Islamic Republic of Iran, thereby strengthening Iran’s influential presence in global politics and increasing Iran’s soft power as an important dimension of power. The research tried to address the pivotal question concerning the role modern media can assume within a country’s diplomatic apparatus. This would involve understanding how media can contribute to advancing national interests and bolstering a country’s influence and authority in the international arena. This research also sought to propose key indicators and strategies for advancing Iran’s digital diplomacy initiatives.Literature ReviewNumerous case studies and comparative analyses have explored digital diplomacy, underscoring the significant impact of social media in international diplomacy. However, despite the close interconnection of technology, diplomacy, and soft power, there is a lack of research that systematically situates these three domains within a theoretical framework and examines international relations theories by considering the role of modern media on the power-building capacity of diplomacy.In the article titled “Shaping Public Diplomacy through Social Media Networks in the 21st Century,” Costa (2017) posits that the Internet and information and communication technology have significantly influenced the definition and performance of public diplomacy. In “Foreign Policy in an Era of Digital Diplomacy,”Adesina (2017) draws the conclusion that digital diplomacy and internet-based activities play a vital role in effectively communicating a government’s foreign policy stances to both domestic and international audiences.  In the article titled “Twitplomacy: Social Media as a New Platform for Development of Public Diplomacy,” Su (2015) argues that the impact of Internet users on the diplomatic agenda can complement political concepts. Considering the role of social media in the public diplomacy of the Islamic Republic of Iran, Ameli (2017) asserts that emerging social media technologies will play a central role in diplomacy by influencing social space.Ganjidoust (2008) focuses on the profound impact of information and communication technology in the field of diplomacy. The author contends that diplomacy has experienced greater influence from technological advancements compared to other domains, primarily because of its heavy reliance on the fundamental components of information and communication. According to Ganjidoust, the developments of the information age have brought about significant transformations in both the form and substance of diplomacy.Materials and MethodsThe Delphi technique was employed for identifying indicators, while the Dimetal technique was utilized for modeling. The study used Partial Least Squares technique to test the exploratory model and analyze the reciprocal influence between variables.ConclusionThe findings revealed that modern media plays a pivotal role as a complete mediator in the transfer of power to diplomacy. Through online communication, new media platforms foster interaction and networking among users. They employ activism, imagery, and psychological operations to craft their desired narrative, thus reinforce user engagement and convergence through orienting and streamlining, Ultimately, by fostering a sense of belonging, they establish identity and create opportunities within the system of diplomacy.To succeed in public diplomacy, particularly in the realm of digital diplomacy, requires a comprehensive strategy encompassing strategic goals, strategic priorities, and executive guidelines to attain the strategic goals. Concerning the Islamic Republic of Iran, the strategic goals are as follows: Making a powerful image of Iran, national branding of Iranian–Islamic identity, informing people about the policies, beliefs, and values of Iranians, and introducing opportunities and strengths. The strategic priorities of the digital diplomacy of the Islamic Republic of Iran include Interacting with citizens and foreign populations to foster and enhance mutual relations, providing transparent information and swift responses to counter misinformation, combating online hooliganism, presenting leadership guidelines, and engaging in social listening and social monitoring. Without a thorough analysis and practical solutions to this question, it is not possible to address the needs of audience satisfactorily. The assessment of attitudes, questions, and challenges is the most critical aspect which guides the subsequent actions. Concerning interaction, it is recommended to interact with influencers, as well as political, religious, cultural, and national figures, to clarify ambiguities and foster constructive dialogues through the dissemination of pre-prepared images, messages, and video clips. Moreover, regular evaluation of the outcomes on the basis of a theory of structures and processes can help ensure the effectiveness of digital diplomacy and coordination.